2020
DOI: 10.3389/fvets.2020.00521
|View full text |Cite
|
Sign up to set email alerts
|

ONE Health Approach to Address Zoonotic Brucellosis: A Spatiotemporal Associations Study Between Animals and Humans

Abstract: Background: Brucellosis is one of the most significant zoonosis over the world, threatening both veterinary and human public health. However, few studies were focused on nationwide animal brucellosis and made association with human brucellosis. Methodology and Principal Findings: We conducted a bilingual literature search on Brucella or brucellosis in China on the two largest databases (China National Knowledge Infrastructure and PubMed) and conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…The authors concluded that numerous animal reservoirs were a potential reason for the continuous circulation of the brucellosis in the examined countries, while the B. abortus strains were dominated in these countries and spreading within the national borders (23). In addition, using descriptive analysis and meta-analysis approaches, Zhou et al reported very recently that dogs and yaks were the leading reservoirs and emerging hosts for Brucella transmission in China (24). Meanwhile, the authors inferred that humans probably get infected along with different kinds of animal species, among which the sheep and goats were likely at the highest risks (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that numerous animal reservoirs were a potential reason for the continuous circulation of the brucellosis in the examined countries, while the B. abortus strains were dominated in these countries and spreading within the national borders (23). In addition, using descriptive analysis and meta-analysis approaches, Zhou et al reported very recently that dogs and yaks were the leading reservoirs and emerging hosts for Brucella transmission in China (24). Meanwhile, the authors inferred that humans probably get infected along with different kinds of animal species, among which the sheep and goats were likely at the highest risks (24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using descriptive analysis and meta-analysis approaches, Zhou et al reported very recently that dogs and yaks were the leading reservoirs and emerging hosts for Brucella transmission in China ( 24 ). Meanwhile, the authors inferred that humans probably get infected along with different kinds of animal species, among which the sheep and goats were likely at the highest risks ( 24 ). The aforementioned studies, as well as the ligatures, e.g., a recent report from our collaborators ( 25 ), consistently demonstrated the significance of the One Health concept and recommended implementing it to disrupt the Brucella transmission chain between animals and humans, as well as to strengthen the close collaboration between the local and public partnerships.…”
Section: Discussionmentioning
confidence: 99%
“…Brucella infects animals and human beings and causes Brucellosis ( Atluri et al, 2011 ), a major zoonotic disease endemic in more than 170 countries and regions of the world ( Avilacalderon et al, 2013 ). Brucellosis is classified as an important reemerging disease of humans and animals in China ( Zhou et al, 2020 ), where it has shown an upward trend in recent years ( Zheng et al, 2018 ). At present, Brucellosis has been reported in many mammals ( Moreno, 2014 ); except for some antibiotics and corticosteroids, there is no effective specificity treatment for the human brucellosis.…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis, also known as Malta fever, undulant fever, and Mediterranean fever, is one of the most prevalent zoonotic diseases worldwide. It is caused by a group of gram-negative bacteria of the genus Brucella [1] and transmitted to humans by direct ingestion of row animal products such as unpasteurized milk or contaminated dairy products, undercooked meat from infected animals, or contact with their secretions [1,2].…”
Section: Introductionmentioning
confidence: 99%